2003
DOI: 10.1034/j.1478-3231.2003.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 8‐hydroxy‐2′‐deoxyguanosine in chronic liver disease and hepatocellular carcinoma

Abstract: Reactive oxygen species may be involved in the progression of chronic liver disease and the occurrence of hepatocellular carcinoma (HCC). To clarify whether clinicopathological findings in liver diseases are related to oxidative DNA damage, hepatic expression of the 8-hydroxy-2'-deoxyguanosine (8-OHdG) was examined in 75 liver disease patients, which included 32 chronic hepatitis (CH), 13 liver cirrhosis (LC) and 30 HCC patients. The CH patients had higher 8-OHdG-positive hepatocytes than LC (P < 0.05). In CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 30 publications
5
44
0
3
Order By: Relevance
“…AST activity in the plasma of cholangiocarcinoma patients was much higher than that in healthy subjects. This result is supported by a previous report showing that the number of 8-oxodG-positive hepatocytes was associated with AST activity in liver diseases and hepatocellular carcinoma (34). These findings can be explained by assuming that an increase in reactive oxygen species not only causes DNA damage but also induces hepatocyte injury, resulting in increased hepatobiliary enzyme activity.…”
Section: Discussionsupporting
confidence: 80%
“…AST activity in the plasma of cholangiocarcinoma patients was much higher than that in healthy subjects. This result is supported by a previous report showing that the number of 8-oxodG-positive hepatocytes was associated with AST activity in liver diseases and hepatocellular carcinoma (34). These findings can be explained by assuming that an increase in reactive oxygen species not only causes DNA damage but also induces hepatocyte injury, resulting in increased hepatobiliary enzyme activity.…”
Section: Discussionsupporting
confidence: 80%
“…Previous reports have noted the high expression of 8-OHdG in the livers of chronic viral hepatitis patients (20,21), and our results are consistent with these reports. Recent studies have shown that high expression of 8-OHdG in livers with CH-C predicted the development of primary hcc (33,34) and also postoperative recurrence (35,36), suggesting the association of 8-OHdG and carcinogenesis in livers with CH-C.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated that 8-OHdG is implicated in carcinogenesis (17,18) and hepatocarcinogenesis (19). 8-OHdG is induced during liver DNA damage (19) and expressed in livers with chronic hepatitis c (CH-C) (20) and chronic hepatitis B (CH-B) (21). 8-OHdG, a good marker of oxidative dna damage, is thought to be involved in hepatocarcinogenesis in the setting of chronic viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…34 Hepatic fibrosis is initiated by damage to hepatocytes that results in the recruitment of inflammatory cells and the activation of kupffer cells, which subsequently lead to enhanced production of profibrotic cytokines such as TNFα and TGF-β, 60 DNA damage is a common feature in various forms of chronic liver diseases. 29,61,62 DNA damage was evident during liver fibrosis and was also shown to correlate with liver fibrosis as assessed by serum hyaluronic acid, platelet count, and histological staining score. 29,[62][63][64][65] In the current study, DNA damage, as evident by higher H2AX phosphorylation on Ser139 as well as the accumulation of PCNA, was enhanced in WT mice fed with HCD compared with iNOSdeficient mice.…”
Section: Discussionmentioning
confidence: 99%